Effect of potentially chromogenic beverages on shear bond strength of acrylic denture teeth to heat-polymerized denture base resins - Karin Hermana Neppelenbroek; Vanessa Migliorini Urban; Denise Gusmao de Oliveira; Vinicius Carvalho Porto; Hercules Jorge Almilhatti; Nara Hellen Campanha (Wolters Kluwer Medknow Publications, 2016)
Background: Detachment of denture acrylic resin artificial teeth from denture base resin is one of the most common problems presented by denture wearers. Purpose: This study investigated the shear bond strength (SBS) and fracture type of bonding interface of two commercial acrylic teeth (Vipi Dent Plus e Biolux) to two denture base resins (Vipi Cril e Lucitone 550) after immersion in potentially chromogenic beverages (coffee, cola soft drink, and red wine) or control solution (distilled water). Materials and Methods: Maxillary central incisor acrylic teeth were placed at 45° to denture base resin and submitted to short polymerization cycle according to manufacturers. Specimens were divided according to the combination tooth/resin/solution (n = 8) and submitted to bond strength tests in a universal testing machine MTS-810 (0.5 mm/min). Subsequently, fracture area was analyzed by stereomicroscope at a magnification of ×10 and categorized into adhesive, cohesive, or mixed failure. Results: The bond strength of teeth/denture base resins interface was not significantly affected by tested solutions (P > 0.087), except for Biolux teeth immersed in coffee (P < 0.01). In all conditions, the Vipi Dent Plus teeth showed higher bond strength to Lucitone and Vipi Cril resins when compared to Biolux teeth (P < 0.003). All specimens' failure modes were cohesive. Conclusions: The SBS of acrylic teeth to denture base resins was not generally influenced by immersion in the tested staining beverages.